Evolution actuelle du modèle urbain colonial français à travers la place et les fonctions du végétal dans la ville de Toliara (Sud-Ouest Madagascar) - Aude Nuscia Taïbi; Mustapha El Hannani; Félicitée Rejo-Fienena (VertigO)
This study of the urban vegetation of Toliara, city located in a semi-arid area in the Southwest of Madagascar, helps understand specific vegetation issues by exploring its typology and various functions, as well as its changes since the French colonial period. It also helps define those issues that are specific to a Southern city, first in a colonial context, then in a non-colonial one. The methodology is based on an in-situ field analysis (2016) combined with aerial (1949) and satellite remote sensing (2015).